Booktube: comunicar a literatura pela via dos afetos - Mickael Braga Barbieri (2019)
This research studied how affects are shown in the sharing of literary experiences in the online booktube community. Booktubers are readers who post videos in platforms such as YouTube aiming at sharing personal impressions arising before, during, and after reading. To carry out this research, the channel of the booktuber Tatiana Feltrin was chosen as the very object of the research for its representativeness of the phenomenon. Tiny Little Things, or just TLT, as the channel is known, has existed for more than ten years. Having as theoretical framework the concepts of reading mediation (PÉTIT, 2009), ordinary affects (STEWART, 2007), and personal resonance (SEILMAIN, 1989), this research aimed at capturing the affective responses emerging from the practice of literary reading as well as the controversies arising from the contact of the booktubers world with the literary criticism and the publishing market. Having I myself become a booktuber in the course of the research, I could realize subtilties that I would never had noticed handling such a complex and challenging phenomenon as the booktube without any involvement. This research resulted in a first-person (or immersive) experience the main outcome of which was an affective writing dealing with affects as a means of conveying knowledge in an emotive fashion.